Alfabetização e gêneros textuais : um estudo da canção como proposta didática - Florentino, Poliana Rodrigues (2018)
The present research of bibliographical character reflects on the enunciative theory of Bakhtin, especially with regard to the textual genres and the possible links with the processes of acquisition of reading and writing, highlighting in such context the role of the song genre. The work is linked to the research line "Languages, Culture and Knowledge Construction: Historical and Contemporary Perspective" and to the Literacy and Literacy study group (ALFALE) of the Post-Graduate Program in Education of the University Campus of Rondonópolis, Federal University of Mato Grosso (PPGEdu / CUR / UFMT). Literacy is approached from the perspective of textual genres as teaching objects, a proposal that has been consolidating in the contemporary world. In this way, the song was chosen as a genre to be analyzed, so it reveals aesthetic, social, affective, and logical possibilities, as it presents statements and no more syllables or loose words, in the literacy routines. It is also intended to discuss the historical path of literacy, its conflicts, tensions, sound approaches, theoretical and methodological advances, contributing in Mendonça (2011), Marcuschi (2008), among others; for reflection on genres, the contributions of authors such as Dolz, Schneuwly, Noverraz (2004), Mortatti (2017), Soares (2004), Bakhtin (2011); with regard to the musical language, stands out Gordon (2000) and Jeandot (1997). As a general objective, we sought to reflect on the teaching of reading and writing, investigating the links between literacy concepts, textual genres, nature of the song and the didactic sequence proposed by Dolz, Schneuwly, Noverraz (2004), on this occasion oriented by the song and the prospect of literate literacy. In order to relate, illustrate and consolidate these propositions, a didactic unit (sequence) was developed for literacy classes of the first year – first cycle – Elementary School, in which gains are verified for the pedagogical practices intended with the effort of the search. The course of work revealed how challenging the theme is, because of the richness, complexity and effectiveness of the song genre as an object of instruction in literacy routines.